ANALISIS PENYIMPANAN DOKUMEN REKAM MEDIS DI RSUD PASAR MINGGU - Arfiandi; Irda Sari (Bajang Institute, 2021)
Medical records are files containing records and documents about the patient's identity, examination, treatment, actions, and other services that have been provided to the patient. A storage system is an activity to store medical records in order to protect them from physical damage and the contents of the documents. The system of storing medical record documents is one of the most important factors in the provision of services in hospitals. The medical record document storage system provides data availability about all services that have been provided to patients. The purpose of this study is to analyze the storage of medical record documents in sunday market hospitals. This type of research is descriptive using qualitative approach. The population of this study was all officers in the storage of medical records documents numbered four people. The sample of this study is the entire population that exists. The data collection of this study was conducted by researchers by interviewing and observation. The validity of the data using source triangulation is to compare the circumstances and perspective of a person in this case the officer storing medical records documents with superiors or officers in other parts of the medical record installation and comparing the results of interviews with a related document.. The results of this study storage system using a centralization system with filing location is still scattered in several storage places and the system alignment terminal digit filling system. The average time to provide medical records for new patients is 8 minutes, the old patient reaches 20 minutes.